Proses Treatment Dengan Menggunakan NaOCl Dan H2SO4 Untuk Mempercepat Pembuatan Bioetanol Dari Limbah Rumput Laut Eucheuma Cottonii - Winjaya Putra, I Nyoman; Wijaya Kusuma, I Gusti Bagus; Suprapta Winaya, I Nyoman (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011, 2012)
The fermentation process of the waste of Eucheuma cottonii seaweed to become bioethanol can beaccelerated by providing special treatment, such as delignification process using NaOCl and immersion byusing a mixture of H2SO4 for different variations. The fermentation process is also be done by using the yeast ofSaccharomyces cerevisiae with a variety of mixtures, to determine the rate of bioethanol fermentation.In this study NaOCl has been used with variation of 0.25%, 0.50% and 0.75%. H2SO4 is used with aconcentration of 0.5% and the variations of Saccharomyces cerevisiae yeast with a ratio of 1: 0.0015; 1: 0.003;1: 0.0045; 1: 0.006 and 1: 0.0075 for every kilogram of waste Eucheuma Cottonii and yeast, and withfermentation time of 3, 6 and 9 days. As a comparison is the same treatment, but without the use of H2SO4.Based on the research, the following results obtained. The highest rate of bioethanol fermentation is4.4% per day and the highest levels of ethanol produced is 14.0%. This is achieved for where each kilogram ofwaste of Eucheuma cottonii is delignificated with a concentration of 0.5% NaOCl followed by a treatment inphysics, with the variations of yeast 1: 0.006 and with a time of fermentation for 3 days.
Keywords: Bioethanol,ragi,fermentasi,mempercepat proses, limbah euheuma cottonii, NaOCl, H2SO4